THE SHELF OF THE KAMCHATSKII CAPE, EASTERN KAMCHATKA, IN THE LATE PLIOCENE AND EARLY QUATERNARY (OLKHOVAYA TIME) - Basilyan A.E.; Bylinskaya M.E. (My University, 1997)
The study of Pliocene-Quaternary sediments of the Kamchatskii Cape and the paleoecologic analysis of associated mollusks and foraminifers resulted in distinguishing the early and late Ol'khovaya transgressions. During the early Ol'khovaya transgression, approximately from 2 to 1.5 Ma, the sea-level rise reached at least 120 m. At the maximum of the early Ol'khovaya transgression, the Kamchatskii Cape represented a shelf of submeridional extension over 15 km wide. The depth ranged from 0 to more than 500 m on the continental slope. The most likely bottom water temperatures at a depth exceeding 30-40 m, were relatively stable. They ranged from -1.5 to +1.8°C on the shelf and were approaching 2°C on the continental slope. It was elucidated that the early Ol'khovaya transgression was accompanied by a slight climatic warming. The late Ol'khovaya transgression occurred from 0.73 to 0.3 Ma and was no less significant.
Keywords: Quaternary; Pliocene; Cenozoic::Quaternary; Cenozoic::Neogene::Pliocene; Кайнозой::Четвертичная; Кайнозой::Неоген::Плиоцен